Bali Tolak Reklamasi: The local adoption of global protest. (June 2020) - Bräuchler, Birgit
Diverted by the virality of social media and the powerful visibility of contemporary global protest, social movement research started to loose sight of the invisible and silent aspects of mobilization and underlying collective identities. Looking at a Balinese protest movement against land reclamation whose anti-capitalist and performative character remind of recent transnational protest, this article refocuses on collective identity and examines the local adoption of global protest. It analyses the evolving actor landscape and the negotiation processes between different cultures, ecologies, generations, media and networking strategies that prominently shape the Bali movement. The article conceptualizes the movement as an emerging information ecology and tracks its entanglements with local identity, national power politics and global activism through a culture and transmedia approach. It thus analyses the loud and the silent side of the protest and the movement's decision-making strategies that involve human and non-human agency, an aspect that is largely missing in current social movement debates. Going beyond simplified notions of strong leadership or leaderless networks, it tracks the difficult balancing acts between openness and closedness, between an ideally consensual and inclusive movement and the necessity to make strategic decisions in a specific local, national and transnational setting.